Representing aspiration in South African television: negotiating space, movement, and value - Rikhotso, Matimu Freddy (Centre for Film and Media Studies, 2022)
The rural South African environment in its many representations across television and documentary forms part of a continuously complex conversation. The ways in which fictional shows such as Generations (SABC1), compared to shows like Giyani: Land of Blood (SABC2) and The Herd (Mzansi Magic) have approached the representation of the rural environment, creates a new lens from which to look academically at the representation of rural areas in South Africa. Furthermore, the representation of aspiration in Giyani: Land of Blood and The Herd speaks to a unique shift in the treatment of the fictional stories we have seen in the past in local television shows. This paper analyses these two shows in conversation with my documentary film, Ndhawu which facilitates a conversation around space, identity and aspiration. This qualitative investigation seeks to look critically at the content of Giyani: Land of Blood, The Herd and my documentary film Ndhawu through textual analysis. This analysis, and the critical reflection on Ndhawu, will be steppingstones to supporting the argument that there is a new type of representation that we not only see of rural South Africa, but also of the aspirations of the inhabitants of those areas